Impact of the COVID-19 crisis on learning, teaching and facilitation of practical activities in science upon reopening of Irish schools. Issue 2 (3rd April 2021) - Chadwick, Ruth; McLoughlin, Eilish
Abstract : In September 2020, Irish schools reopened following their emergency closure due to the COVID-19 crisis. Measures were put in place to minimise the risk of transmission of the virus within schools and communities. However, these measures were likely to impact on teachers' capacity to facilitate learning in science, particularly the practical and investigative aspects of the Irish curriculum. This research explores the impact of the measures in place to limit virus transmission on teaching and learning in science, particularly on practical activities. The period of focus is the three months (September to November 2020) following the school closures. The research aims to highlight the implications of the COVID-19 crisis on science teaching and learning in Irish schools. The research will also provide recommendations to lessen the impact on primary and second-level science education to improve student learning and engagement in science.